2018
DOI: 10.1186/s12967-018-1669-2
|View full text |Cite
|
Sign up to set email alerts
|

iTRAQ-based quantitative analysis of age-specific variations in salivary proteome of caries-susceptible individuals

Abstract: BackgroundHuman saliva is a protein-rich, easily accessible source of potential biomarkers for the diagnosis of oral and systemic diseases. However, little is known about the changes in salivary proteome associated with aging of patients with dental caries. Here, we applied isobaric tags for relative and absolute quantitation (iTRAQ) in combination with multiple reaction monitoring mass spectrometry (MRM-MS) to characterize the salivary proteome profiles of subjects of different ages, presenting with and witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 35 publications
(41 reference statements)
3
29
0
Order By: Relevance
“…Next-generation sequencing technologies have been successfully applied in oral microbial analysis [ 12 14 ]. The isobaric tags for relative and absolute quantitation (iTRAQ) is a new technique which uses isotopes to label polypeptides for comparing proteomes quantitatively [ 15 , 16 ]. To the best of our knowledge, previous studies of caries-related microbiome and proteome were detached.…”
Section: Introductionmentioning
confidence: 99%
“…Next-generation sequencing technologies have been successfully applied in oral microbial analysis [ 12 14 ]. The isobaric tags for relative and absolute quantitation (iTRAQ) is a new technique which uses isotopes to label polypeptides for comparing proteomes quantitatively [ 15 , 16 ]. To the best of our knowledge, previous studies of caries-related microbiome and proteome were detached.…”
Section: Introductionmentioning
confidence: 99%
“…As concerns the organic components, in addition to the salivary concentration, they also measured the total amount secreted into the oral cavity, concluding that in the elderly the total values of most salivary components decrease parallel to the salivary flow rate 22 . In 2014, Nassar et al found a decrease in salivary calcium level in elderly people compared to young 23 . Conversely, Sevon et al reported elevated levels of salivary calcium in elderly women, with a peak at around the age of 50 years, compared to that of young women.…”
Section: Changes In Salivary Compositionmentioning
confidence: 99%
“…On the other hand, in their 2014 study Nassar et al assessed that the salivary buffering capacity is not related to age. As most of the salivary bicarbonate is secreted by the parotid gland, the parotid gland function seems to be not prejudiced by aging 23 . A lower salivary concentration of basic fibroblast growth factor (bFGF) has been reported in elderly subjects.…”
Section: Changes In Salivary Compositionmentioning
confidence: 99%
“…With the rapid development of proteomics technology and the application of high resolution mass spectrometry, isobaric tags for relative and absolute quantification (iTRAQ) is currently the most widely used technology in quantitative proteomics [6]. The core principle of iTRAQ is polypeptide labeling and quantification, which resolves quantitative changes in protein intensities with high sensitivity, accuracy, and reproducibility [7]; it is widely used in protein biomarker validation to support preclinical and clinical studies [8].In a previous iTRAQ technology study of silicosis, researchers employed SiO 2 to stimulate raw264.7 cells [9], and TGF-β to stimulate lung fibroblasts [10].…”
Section: Introductionmentioning
confidence: 99%